Gellan-Based Hydrogel as a Drug Delivery System for Caffeic Acid Phenethyl Ester in the Treatment of Oral Candida albicans Infections - Maíra Terra Garcia; Paulo Henrique Fonseca do Carmo; Lívia Mara Alves Figueiredo-Godoi; Natália Inês Gonçalves; Patrícia Michelle Nagai de Lima; Lucas de Paula Ramos; Luciane Dias de Oliveira; Alexandre Luiz Souto Borges; Anita Shukla; Juliana Campos Junqueira (MDPI AG, 2024)
Candida albicans can cause various types of oral infections, mainly associated with denture stomatitis. Conventional therapy has been linked to high recurrence, toxicity, and fungal resistance, necessitating the search for new drugs and delivery systems. In this study, caffeic acid phenethyl ester (CAPE) and gellan gum (GG) were studied as an antifungal agent and carrier system, respectively. First, we observed that different GG formulations (0.6 to 1.0% wt/vol) were able to incorporate and release CAPE, reaching a controlled and prolonged release over 180 min at 1.0% of GG. CAPE-GG formulations exhibited antifungal activity at CAPE concentrations ranging from 128 to >512 µg/mL. Furthermore, CAPE-GG formulations significantly decreased the fungal viability of C. albicans biofilms at short times (12 h), mainly at 1.0% of GG (p < 0.001). C. albicans protease activity was also reduced after 12 h of treatment with CAPE-GG formulations (p < 0.001). Importantly, CAPE was not cytotoxic to human keratinocytes, and CAPE-GG formulations at 1.0% decreased the fungal burden (p = 0.0087) and suppressed inflammation in a rat model of denture stomatitis. Altogether, these results indicate that GG is a promising delivery system for CAPE, showing effective activity against C. albicans and potential to be used in the treatment of denture stomatitis.